Morphological records of oocyte maturation in the parthenogenetic tick Amblyomma rotundatum Koch, 1844 (Acari: Ixodidae) - Sanches, Gustavo S. [UNESP]; Araujo, Andrea M. [UNESP]; Martins, Thiago F.; Bechara, Gervasio Henrique [UNESP]; Labruna, Marcelo B.; Camargo-Mathias, Maria I. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2012)
Oocyte maturation in the thelytokous parthenogenetic tick Amblyomma rotundatum was examined for the first time using light and scanning electron microscopy. The panoistic ovary lacks nurse and follicular cells and is a single continuous tubular structure forming a lumen delimited by the ovarian wall. Oocytes of tick species are usually classified according to cytoplasm appearance, the presence of germinal vesicle, the presence of yolk granules, and the chorion. However, for this species, we also use oocyte size as an auxiliary tool since most oocytes were in stages I-Ill and were histologically very similar. Oocytes were classified into five development stages, and specific characteristics were observed: mature oocytes with thin chorion, pedicel cells arranged forming an epithelium with two Or more oocytes attached by the same structure, and a large number of oocytes in the process of reabsorption. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Amblyomma rotundatum; Parthenogenesis; Vitellogenesis; Ovary; Histology; Scanning electron microscopy